1976
DOI: 10.1093/jaoac/59.4.770
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Congeners Produced from Ethanol During Whisky Maturation

Abstract: A study was made to determine which congeners are derived from ethanol during maturation of whisky. Radioactive ethanol-1-14C was added to a barrel of new bourbon whisky and the radioactivity of the major individual congeners was determined during the maturation period. During 56 months of maturation, ethanol was transformed into acetic acid, acetaldehyde, ethyl acetate, and ethanol lignin as indicated by their radioactivity. No radioactivity was found in the solids, fusel oil alcohols, or the aromatic aldehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The acetic acid proceed from the distillate, from the oxidation of ethanol via acetaldehyde and also from the oak wood, like the radioactive assay conducted by Reazin et al (1976) has been demonstrated. The acetic acid proceeds from the acetyl groups present in the wood xylans, an important group of wood hemicelluloses (Fengel & Wegener, 1989).…”
Section: Furanic Aldehydes and Acetic Acidmentioning
confidence: 88%
See 2 more Smart Citations
“…The acetic acid proceed from the distillate, from the oxidation of ethanol via acetaldehyde and also from the oak wood, like the radioactive assay conducted by Reazin et al (1976) has been demonstrated. The acetic acid proceeds from the acetyl groups present in the wood xylans, an important group of wood hemicelluloses (Fengel & Wegener, 1989).…”
Section: Furanic Aldehydes and Acetic Acidmentioning
confidence: 88%
“…The evaporation that results in the decrease of ethanol strength and loss of volume of the brandies could result in a concentration effect as reported by Puech et al (1984). Other reactions like the oxidation of some acids with the formation of ketones (Watts & Butzke, 2003), alcohols oxidation (Reazin et al, 1976) acetalization (Puech et al, 1984) and the acid catalysed esterification and hydrolysis of the esters (Nykänen & Suomalainen, 1983) are also reported.…”
Section: Odorant Compounds From the Distillate -Alcohols Esters Termentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidation of alcohols is a known pathway for increasing the contents of aldehydes during ageing of spirits (Reazin et al, 1976). Although oxidation can occur spontaneously, it is certainly accelerated by several adventitious microorganisms (Suomalainen, 1967;Amerine and Ough, 1980); the highest aldehyde levels are apparently attained when yeasts are well within their exponential growth phase (Radler, 1973).…”
Section: Aldehydesmentioning
confidence: 99%
“…Tl'/Tl = 1 + Bm (2) and n D H N = 55.5B (3) where m is the molarity (M/kg HzO) of ethanol, and 55.5 is the molanty of 1 kg of water.…”
Section: N D H N = Nh(th/t? -mentioning
confidence: 99%